Association between intimate partner violence and leukocyte telomere length: a retrospective cohort study of 144 049 UK Biobank participants. (24th April 2023) - Chan, Ko Ling; Lo, Camilla K. M.; Chen, Xiao-Yan; Ip, Patrick; Leung, Wing Cheong; Shiels, Paul G.; Pell, Jill P.; Minnis, Helen; Ho, Frederick K.
Abstract: Aims: Intimate partner violence (IPV) is a public health challenge negatively affecting victims' health. Telomere length (TL), a marker for biological ageing, might be reflective of the mechanisms through which IPV leads to adverse health outcomes. The objective of the current study was to explore the association between IPV and leucocyte TL. Methods: We conducted an analysis using a subset of the UK Biobank ( N = 144 049). Physical, sexual and emotional IPV were reported by the participants. DNA was extracted from peripheral blood leukocytes. TL was assayed by quantitative polymerase chain reaction. We used multivariable linear regressions to test the associations between IPV and TL adjusted for age, sex, ethnicity, deprivation, education, as well as symptoms of depression and post-traumatic stress disorder in a sensitivity analysis. Results: After adjusting for sociodemographic factors, any IPV was associated with 0.02-s.d. shorter TL ( β = −0.02, 95% CI −0.04 to −0.01). Of the three types of IPV, physical violence had a marginally stronger association ( β = −0.05, 95% CI −0.07 to −0.02) than the other two types. The associations of numbers of IPV and TL showed a dose–response pattern whereby those who experienced all three types of IPV types had the shortest TL ( β = −0.07, 95% CI −0.12 to −0.03), followed by those who experienced two types ( β = −0.04, 95% CI −0.07 to −0.01). Following additional adjustment for symptoms of depression and PTSD, the associations were slightly attenuated but the general trend by number of IPVs remained. Conclusions: Victims of IPV, particularly those exposed to multiple types of IPVs, had shorter TL indicative of accelerated biological ageing. Given that all three types of IPV are linked to TL, clinical practitioners need to comprehensively identify all types of IPV and those who received multiple types. Further studies should explore the association of violence with changes in TL over time, as well as to which extent biological ageing is a mechanistic factor.